RELATIONSHIP BETWEEN HEMATOCRIT, PLATELETS AND PLATELET-TO-LYMPHOCYTE RATIO WITH LENGTH OF STAY IN CHILDREN WITH DHF - Sari Rahmayanti (Jurnal Vokasi Kesehatan, 2021)
Dengue Hemorrhagic Fever (DHF) is still health problem in Indonesia. DHF cause big impact to public health and create economic problems. The purpose of this study was to determine the relationship between hematocrit, platelet and platelet-to-lymphocite ratio with the length of stay of children with DHF who were treated at the Sultan Syarif Mohammad Alkadrie Hospital throughout 2019. This study was conducted with cross-sectional design and the data was obtained from the medical records in Sultan Syarif Mohamad Alkadrie Hospital. The sampleâ€™s data was collected using total sampling method with a sample size of 79 people.Â  The data were analyzed using Mann-Whitney test and Pearson test. This study found there is relationship between hematocrit (p=0,000) with length of stay in children with DHF and no significant relationship between platelets (p=0.173) and platelet-to-lymphocyte ratio (p=0.319) with length of stay in children with DHF.